Situation Report: Poland, 18 October 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Walesa's New Team: A Collective Profile Uncertainties about the 1982 Economic Plan an Budget Coal: A Vital Factor in Economic Recovery